2008
DOI: 10.1557/proc-1113-f02-05
|View full text |Cite
|
Sign up to set email alerts
|

High performance polymer/BaTiO3 nanocomposites based on surface-modified metal oxide nanoparticles using functional phosphonic acids for electronic applications

Abstract: Polymer/ceramic nanocomposites provide a means of combining the high permittivities (εr) of metal oxide nanoparticles with the solution-processability and high dielectric strength of polymeric hosts. Simple mixing of nanoparticles and polymers generally results in poor quality nanocomposites due to the agglomeration of nanoparticles and poor miscibility of nanoparticles with host materials. We have shown that surface modification of metal oxide nanoparticles with phosphonic acid-based ligands affords robust su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The microscopy visualization showed that the cellular morphology observed was comparable to that of the control group. As anticipated, BT:Sm NPs demonstrated heterogeneous levels of aggregation (Figure d, shown by black arrows), as previously reported by others. The black dots are higher in cells subjected to uncoated BT:Sm NPs than in cells treated with (PEG)-coated BT:Sm NPs. Consequently, the incorporation of PEG would enhance the solubility of these NPs in physiological fluids.…”
Section: Results and Discussionsupporting
confidence: 85%
“…The microscopy visualization showed that the cellular morphology observed was comparable to that of the control group. As anticipated, BT:Sm NPs demonstrated heterogeneous levels of aggregation (Figure d, shown by black arrows), as previously reported by others. The black dots are higher in cells subjected to uncoated BT:Sm NPs than in cells treated with (PEG)-coated BT:Sm NPs. Consequently, the incorporation of PEG would enhance the solubility of these NPs in physiological fluids.…”
Section: Results and Discussionsupporting
confidence: 85%
“…Atomic or molecular adsorbates including surface ligands [ 101,102 ] and coatings [ 103 ] stabilize the ferroelectricity of nanoscale BaTiO 3 and make it useful to design ferroelectric devices that can operate at the atomic scale. High performance BaTiO 3 nanocomposite materials have been prepared by integrating complementary polymers (polyvinylidene fluoride (PVDF), [ 104,105 ] polyacrylamide, [ 106,107 ] poly(2‐hydroxylethyl methacrylate), [ 108 ] poly(vinylidene fluoride‐hexafluoro propylene) (P(VDF‐HFP)), [ 109,110 ] 2‐[2‐(2‐methoxyethoxy) ethoxy]ethyl} phosphonic acid (PEGPA) [ 102,111 ] with BaTiO 3 . These nanocomposites offer superior performance, processability, and scalability than the pure BaTiO 3 nanostructures.…”
Section: Batio3 Nanoparticlesmentioning
confidence: 99%
“…BaTiO 3 NPs have high surface energy and large surface area which tend to form large aggregates when there are dispersed in aqueous media. [ 111,175 ] Hence these next decades, the hydroxylation of pristine BaTiO 3 surface became a common surface activation method before any surface modification such as functional ligand or core–shell formation with metallic element. [ 81,83,176–178 ]…”
Section: Synthesis and Functionalization Of Batio3 Nanoparticlesmentioning
confidence: 99%
“…Common methods are surface modifier, such as phosphate ester surfactants, silane coupling agent, and polydopamine (PDA) . For instance, Kim reported that BT nanocomposites modified with phosphonic acid ligands leaded to well‐dispersed BT nanocomposite films, which had high dielectric constant, dielectric strength, and energy‐storage capacity. Ramajo studied the influence of silane coupling agents on the microstructure and dielectric behavior of epoxy/BaTiO 3 composites.…”
Section: Introductionmentioning
confidence: 99%